Does highway access influence local employment? Evidence from German municipalities - Luisa Dörr; Stefanie Gäbler (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2022)
We examine how highway accessibility influences local employment outcomes. We exploit the stagewise expansion of the "Baltic Sea highway", the largest contiguous highway construction project in Germany since 1945. Results from difference-indifferences estimations and an event study approach show that highway access influences local employment outcomes in peripheral municipalities within 10 km road distance. Improved accessibility decreases employment by 9%. These effects are driven by reduced commuter flows within the periphery, while we find opposing effects on core municipalities. Improved accessibility also gives rise to a shift of population and economic activity from the periphery to the core, weakening the periphery as a place of work.
Keywords: H54; H71; O18; 330; Highway; infrastructure; accessibility; commuting; employment; municipalities; local governments